A Critical Review of the Equality Iranian God/Goddess ‎with the Gods/Goddess of Greeks Case Study: Vanand, Ashi and Nike - Reza Mehrafarin; Shahin Aryamanesh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the goddesses figures, used in the works of the Parthian and Sasanian periods, is the Greek goddess Nike figure. This goddess figure has been used in the Parthian period on Parthian coins and rock reliefs. In Sasanian era goddess Nike has also been depicted on some rock reliefs. Various views have been expressed about these figures, as some believe that the Parthians with using Greeks iconography, depict the Iranian goddess. So described the Nike goddess in the Parthian period was identical with the Ashi and Vanand. However, the kingdom, as Vologases I, made an outstanding contribution to rebuilding Iranian culture and religions when it came to reign and also tried to eliminate the cultural remains of Greek in Iran. According to the book of Denkard at the time of Vologases, the Avesta text was collected and the Greek names of the cities were renamed by Iranian names‏.‏ For the first time, he also used the Parthian Pahlavi line and fire-altar on his coins, maybe because of the fact that he removed the figure of Nike goddess from his coins. The authors of this paper deal with the‎ figure of Nike goddess among the Greeks and the Seleucid and the Parthian period. Then they examine the views about Nike Goddess expressed on it in Iranian ‎culture. They continue to conclude that the figure of Nike goddess in the Parthian period was not identical with the Ashi and Vanand. For this reason, Vologases I, eliminated the figure of Nike goddess from his coins during his reign with the goal of Persianism and the abandonment of non-Iranian symbols.